A double hetero[4]helicene composed of two phenothiazines: synthesis, structural properties, and cationic states. Issue 97 (13th October 2015) - Sakamaki, Daisuke; Kumano, Daisuke; Yashima, Eiji; Seki, Shu
Abstract : A novel double hetero[4]helicene has been prepared by the tandem oxidative C–N coupling of phenothiazine derivatives. This double helicene exhibited good electron donor properties and easily gave the stable cationic radical salt. Abstract : A novel double hetero[4]helicene consisting of two phenothiazines (1) has been synthesized. The racemization barrier of 1 is high enough for optical separation. We successfully obtained the single crystals of the radical cation salt of1 ˙ +, whose torsion angles were decreased compared to those of the neutral state.